ESTABLISHING A SUSTAINABLE DEVELOPMENT INDICATOR SET INCLUDING ECONOMIC, SOCIAL, AND ENVIRONMENTAL FIELDS IN TAY NGUYEN PROVINCES - Y, Tran Van; Tri, Ngo Dang; Can, Le Thac; Chi, Tran Thuy; Chinh, Nguyen The; Hau, Nguyen Xuan; Hieu, Nguyen Viet; Tuan, Do Quoc; Thinh, Nguyen Viet; Tuan, Nguyen Thanh; Hennessy, James (Vietnam Journal of Earth Sciences, 2014)
A  sustainable  development  indication  set  plays  a  very  important  role  for  assessing,  monitoring  the  sustainable development  status  in  a  region,  supporting  policy,  decision makers to  propose  confident  decisions  to control  economic, social, and environmental themes toward sustainable developmet. The content, procedure, methodology, and methods to establish the sustainable development indicator set in Tay Nguyen (SDI) were figured out; proposing a list of sustainable development indicators for Tay Nguyen consisting of 77 indicators at regional scale, 70 indicators at provincial scale, 49 indicators at district scale. The  SDI could comprehensively show overall development process toward sustainable by 13 themes (economic field - 3 themes; social field - 5 themes; and environmental field - 5 themes). The paper outlined the SDI’s definition and indicated SDI’s significance through linkages between the sustainable development indicators and sustainable development themes.ReferencesLê Thạc Cán, Trần Thùy Chi, Nguyễn Thế Chinh, Nguyễn Viết Thịnh, Ngô Đăng Trí, Nguyễn Thanh Tuấn, Trần Văn Ý và James Hennessy, 2013. Kết quả bước đầu của Đề tài “Nghiên cứu xây dựng Bộ chỉ tiêu phát triển bền vững các lĩnh vực kinh tế xã hội và môi trường các tỉnh Tây Nguyên”, Tạp chí Khoa học Công nghệ Việt Nam, ISSN 1859-4794. No14, 2013, p 61-64. Dhakal S. 2002. Report on Indicator related research for Kitakyushu Initiative. Ministry of Environment, Japan. Harold A. Linstone, Murray Turoff, 2002. The Delphi Method: Techniques and Applications. Hui-Chun Chu, Gwo-Jen Hwang, 2008. A Delphi-based approach to developing expert systems with the cooperation of multiple experts, Expert Systems with Applications, 34(4), 2826- 840. (SCI). Jean Hugé, Hai Le Trinh, Pham Hoang Hai, Jan Kuilman and Luc Hens, 2009. Sustainability indicators for clean development mechanism projects in Vietnam, Springer Netherlands. Environment, Development and Sustainability, August 2010, Volume 12, Issue 4, pp 561-571. Trần Văn Ý, Lê Thạc Cán, Trần Thùy Chi, Nguyễn Thế Chinh, Ngô Đăng Trí, Nguyễn Viết Thịnh, Nguyễn Thanh Tuấn, 2013. Bộ chỉ tiêu phát triển bền vững về các lĩnh vực kinh tế, xã hội và môi trường các tỉnh Tây Nguyên. Kỷ yếu hội thảo quốc tế lần thứ tư, Việt Nam học, Nhà xuất bản Khoa học xã hội, Hà Nội, ngày 26-28/11/2012, tập IV, 386-400. Bộ Kế hoạch và Đầu tư, 2010. Hệ thống chỉ tiêu thống kê quốc gia (Ban hành theo Quyết định số 43/2010/QĐ/TTg ngày 02 tháng 6 năm 2010 của Thủ tướng Chính phủ). UNDP và MPI, 2005. Identification of a sustainable development indicators set and mechanism for building a sustainable development database in Vietnam (Project VIE/01/021 “Implementation of Vietnam Agenda 21”) United Nations, 2007. Indicators of Sustainable Development: Guidelines and Methodologies. Thủ tướng Chính phủ, 2012. Các chỉ tiêu giám sát và đánh giá phát triển bền vững Việt Nam giai đọan 2011-2020 (Ban hành kèm theo Quyết định số 432/QĐ-TTg ngày 12 tháng 4 năm 2012 của Thủ tướng Chính phủ). Thủ tướng Chính phủ, 2013. Bộ chỉ tiêu giám sát, đánh giá phát triển bền vững địa phương giai đoạn 2013-2020 (Ban hành kèm theo Quyết định số 2157/QĐ-TTg ngày 11 tháng 11 năm 2013 của Thủ tướng Chính phủ).